2016
DOI: 10.1136/archdischild-2016-311535.39
|View full text |Cite
|
Sign up to set email alerts
|

Audit of Paracetamol Prescriptions in Paediatric Surgical Patients

Abstract: 100 inpatient prescriptions (71 elective and 29 non-elective) and 35 discharge prescriptions were analysed.1. Weight was annotated for 84% of inpatient prescriptions and 94% of discharge prescriptions; height was not documented for any patient. Therefore data was analysed basing IBW on 50th centile of the UK growth charts.2. The following results are based on IBW: ▸ Six inpatients prescribed oral paracetamol were classified as overweight or obese; doses ranged from 17.4-30 mg/kg/dose. ▸ Four patients prescribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Six studies were identified that provide data on paracetamol dosing patterns in pediatric patients who are overweight or obese. These studies included four retrospective studies conducted in Danish [ 34 ], Middle Eastern [ 35 ], Italian [ 36 ], and American populations [ 37 ], an audit of pain management prescriptions in the United Kingdom [ 38 ], and a survey and observational study of Australian caregivers and pharmacists [ 39 ]. Overall, the studies reported that dosing practices in children who were overweight or obese were variable and findings of incorrect dosing were mixed.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies were identified that provide data on paracetamol dosing patterns in pediatric patients who are overweight or obese. These studies included four retrospective studies conducted in Danish [ 34 ], Middle Eastern [ 35 ], Italian [ 36 ], and American populations [ 37 ], an audit of pain management prescriptions in the United Kingdom [ 38 ], and a survey and observational study of Australian caregivers and pharmacists [ 39 ]. Overall, the studies reported that dosing practices in children who were overweight or obese were variable and findings of incorrect dosing were mixed.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…Three studies reported more frequent overdosing in children who were overweight or obese [ 34 , 38 , 39 ]. The retrospective cohort study conducted at the Danish Children’s Obesity clinic evaluated dosing strategies in 200 overweight or obese children aged 3–18 years from 2007 to 2015.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation